(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2023)
This paper presents a software module made by means of a programmable logic controller and an HMI (Human Machine Interface), designed to control the movement of an electric wheelchair. By developing this module, a major advantage is offered to people with disabilities, who have movement difficulties. By implementing this command on a wheelchair, people can move independently using this machine that can be controlled from a touch screen. In this direction, the user has the possibility to choose the following directions of movement of the car: forward-backward and left-right, as well as the possibility to impose the speed of movement. The software program was created using ladder diagram language, and the user interface is provided through an HMI.